The Influence of Intensity of Social Media Use on the Consumption Behavior of Senior High School 3 Palangka Raya - Rozikin, Achmad Zainul; Sartika, Nyimas Yuhanis (Neraca: Jurnal Pendidikan Ekonomi, 2024)
High school students' consumption behavior is influenced by several factors, one of which is the intensity of social media use. The aim of this research is to find out how much influence the intensity of social media use has on the consumption behavior of students at SMAN 3 Palangka Raya. Data for the two variables (intensity of social media use and consumption behavior) comes from a questionnaire filled out by students of SMAN 3 Palangka Raya. The population of this study was 1635 students, while the sample was 509 students. The sampling technique uses random sampling techniques. The results of this study indicate that consumption behavior can be influenced by the intensity of social media use.